Dignity and its discontents: Towards an abolitionist rethinking of dignity. (January 2021) - Simon, Jonathan
As we approach the decade anniversary of the US Supreme Court decision in Brown v. Plata (2011), it is perhaps a good time to take stock of some of the optimism expressed by this author (Simon, 2014) that the landmark prisoners' rights decision, with its stark condemnation of the toxic combination of chronic illness, medical neglect, and overcrowding so typical of American prison systems in the era of mass incarceration, and its rhetorical invigoration of 'dignity' as a constitutional value, could play a role in taming mass incarceration in the United States. In doing so, part of the inquiry is juridical and jurisprudential. Did the opinion move the court system towards more protection of human rights for prisoners? The second aspect of the question is cultural and political. At a time of unprecedented public interest in reforming the criminal legal system in the United States, has the language or rhetoric of 'human dignity, ' along with the problems of illness and overcrowding that the Plata case called national attention to, played a role in the foment? The Black Lives Matter movement, a major force in the street protests against policing in the summer of 2020, emerged just two years after Plata and, completely independently, has revitalized abolition discourse in the United States, leading to popular calls to 'defund' the police. To what extent should abolition and other goals of the movement for racial justice, supplant human dignity, with its liberal legal genealogy, as a meaningful lodestar for legal and political efforts to end mass incarceration? As an essay in normative sociological jurisprudence, my answers will be both descriptive and prescriptive.